Women’s representations in Saudi Arabia: the case of universities’ online discourses - Samar Fahad A. Alkhalil (Cogent Arts & Humanities)
Saudi society is undergoing a shift towards greater inclusivity, with men and women gaining access to diverse job and education opportunities. These changes are reflected in Saudi universities, where women now hold prominent positions, potentially influencing institutional language use – an area that remains underexplored. This study examines the linguistic representation of women in the X posts (formerly Twitter) of two leading Saudi universities. A corpus of 120 posts referencing women was analysed using quantitative and qualitative content analysis. The findings reveal a predominant use of a feminine approach, where women are explicitly referenced through their names and gender-marked nouns, positioning them as leaders, celebrating their achievements and emphasising institutional support. Nonetheless, a masculine approach persists, characterised by generic masculine forms to referring to both genders, masculine terms used specifically for women, and male-first ordering in gender pairings, reflecting enduring gender asymmetries. This linguistic bias is partially mitigated by the adoption of impartial approaches, such as gender-neutral terms and collective nouns inclusive of both genders. Overall, the study highlights the complex negotiation between traditional gendered language practices and emerging discourses of women’s empowerment in Saudi higher education, offering insights relevant to gender policy and sociolinguistic research in Arabic-speaking contexts.